A study of safety and security of pedestrians travelling towards the Bellville, Claremont and Mitchells Plain public transport interchanges in the Cape Town municipal area - Renee, Petersen (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.